Affinity Laminated Chromatography Membrane Built‐in Electrodes for Suppressing Polysulfide Shuttling in Lithium–Sulfur Batteries. Issue 2 (19th November 2019) - Wang, Yuxiao; Yu, Ying; Tan, Yeqiang; Li, Tianyu; Chen, Yanbing; Wang, Shuang; Sui, Kunyan; Zhang, Hongzhang; Luo, Yang; Li, Xianfeng
Abstract: Lithium–sulfur (Li–S) batteries are promising candidates for energy storage, but suffer from capacity and cycling challenges caused by the serious shuttling effect of polysulfide (PS) ions. To address these issues, a sodium alginate (SA)‐derived affinity laminated chromatography membrane built‐in electrode is designed. This is the first attempt to utilize this type of membrane, which is widely used for the selective adsorption of proteins, in the battery field. An ordered multilayer structure throughout the electrode can easily be obtained, and the number of membrane layers can be also conveniently controlled by varying the cross‐linking time of SA. The PS shuttling effect is efficiently suppressed and the permeability of PSs is reduced by enveloping the carbon/sulfur powder in ultrathin laminated chromatography membranes. As a result, these designed electrodes deliver a superhigh initial capacity of 1492 mA h g −1, with a capacity retention almost 20% higher than the contrast. This low‐cost and easily mass‐producible strategy inspired by affinity chromatography is expected to effectively solve the PS shuttling problem toward high‐loading and long‐lifetime Li–S batteries in practice. Abstract : Affinity membrane chromatography is a technology that utilizes multiple layers of separators. Here, the suppression of polysulfide shuttling is demonstrated found in a Li–S battery using this technology. These mass‐producible affinity membrane‐embedded electrodes are constructed in situ with sodium alginate via simple cross‐linking, which can decrease the permeability of polysulfides by almost 2 orders of magnitude.